Impact of course length on swimming performance across age groups and swimming strokes - Iglesias García, J.; Hermosilla-Perona, F.; Gonjo, T.; Juárez Santos-García, D. (Frontiers in Sports and Active Living, 2025)
Introduction: Swimmers typically achieve faster times in the same distance events in short course (SC) than in long course (LC) due to the higher number of turns in SC; however, the influence of age and sex on performance differences between SC and LC events remains unclear.